Agile talent - Younger, Jon (Harvard Business Press, 2016)
This book delivers that roadmap. It tells you how to assess, choose, attract, develop, support, and retain your external talent. Authored by thought leaders and bestselling authors in leadership and talent management who teach and consult globally, Agile Talent reveals how companies such as Apple, Uber, Airbnb, Google, IBM, and Bain Capital organize and manage new forms of talent in innovative ways. Supported by survey data and packed with tools and templates for applying these ideas, this book is the ultimate guide for winning the next war for talent.